Types and Toxicity Levels of Pesticides: A Study of an Agricultural Area in Brebes Regency - Budiyono Budiyono; Suhartono Suhartono; Apoina Kartini (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Previous studies found that young children, children, pregnant women, and farmers are at risk of pesticide exposure. Organophosphate pesticides are detected in children's urine, but other types of pesticides, their toxicity classification, and their toxicity level have not been identified. Hence, this study aims to identify types and toxicity levels of pesticides that are possible causes of health problems in an agricultural area. Methods: The population of the study were 1,017 households in two villages of an agricultural area of Brebes Regency, Indonesia. The data were collected from 166 participants using a cross-sectional design involving questionnaires to identify the characteristics of the respondents and observations to identify the pesticide, pesticide packaging, and pesticide residue in their houses. The toxicity levels of the pesticides were identified based on the pesticide toxicity classification recommended by the World Health Organization (WHO). Potential health problems due to pesticides were subsequently identified based on literature reviews. Results and Discussion: According to the results, organophosphate, carbamate, and pyrethroid pesticides were found in 30.7% of the respondents' houses. The toxicity levels of the pesticides ranged from highly hazardous (Ib) to unlikely presenting acute hazard (U). The potential health problems due to pesticides varied from poisoning symptoms to genetic disorders and polymorphisms. Conclusion: There were three types of pesticides with toxicity levels ranging from highly hazardous to unlikely presenting acute hazard in the agricultural area in Brebes Regency